CORONARY ARTERY DOMINANCE: CT ANGIOGRAPHIC FINDINGS IN 1000 PATIENTS - Khan, Muhammad Nadir; Adil, Muhammad; Shabbir, Muhammad; Aziz, Sohail; Hamid, Shabnam (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the pattern of coronary artery dominance in patients undergoing computerized tomography coronary angiography (CTCA). Study Design: Descriptive study Place and Duration of Study: Catherization laboratory Armed Forces Institute of Cardiology, Rawalpindi from Aug, 2012 to Aug, 2013 over a time period of one year. Patient and methods: All 1000 consecutive patients who presented to Catherization laboratory for CTCA for various indications were included in our study. All the patients were selected by non-probability purposive sampling technique. Patients with previous coronary graft bypass surgery, supraventricular arrhythmias, renal insufficiency, allergy to contrast agents, epilepsy, claustrophobia and pregnancy were excluded from the study. All the CTCA images were evaluated in terms of coronary artery dominance and findings were recorded by a checklist. Patients demographic and CT angiography findings were recorded. Finally data was analyzed by using SPSS version 21. Various descriptive statistics were used to calculate frequencies, percentages, means and standard deviation. The numerical data such as age were expressed as Mean ± Standard deviation while the categorical data were expressed as frequency and percentages. Results: A total of 1000 patients undergoing CTCA were included in this study out of which 705(70.5%) were males and remaining 295(29.5%) were females with male to female ratio of 2.54:1. Age range of the patients was 16-95 years with mean 51.89±12.59 years. Right coronary artery was dominant in 849(84.9%) patients while left coronary artery was dominant in 113(11.3%) patients and 38(3.8%) patients were co-dominant. Conclusion: Right coronary artery is dominant in most patients while co-dominance is least and there is no significant association between coronary artery dominance and gender.